2010
DOI: 10.1186/1475-2875-9-28
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of two malaria rapid diagnostic tests in children under five years of age, with follow-up of false-positive pLDH test results, in a hyperendemic falciparum malaria area, Sierra Leone

Abstract: BackgroundMost malaria rapid diagnostic tests (RDTs) use HRP2 detection, including Paracheck-Pf®, but their utility is limited by persistent false positivity after treatment. PLDH-based tests become negative more quickly, but sensitivity has been reported below the recommended standard of 90%. A new pLDH test, CareStart™ three-line P.f/PAN-pLDH, claims better sensitivity with continued rapid conversion to negative. The study aims were to 1) compare sensitivity and specificity of CareStart™ to Paracheck-Pf® to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 30 publications
6
69
2
Order By: Relevance
“…The high sensitivity achieved using this CareStart Test was quite comparable with previous CareStart Tests that were reported to have 99.4% in Wondogenet, 14 95% in Kola Diba, 15 94.91% in Karachi, 16 99.4% in Sierra Leone, 17 and 100% in Ghana 18 ; however, it was higher than the study reported (89.68%) in China-Myanmar. 19 The higher sensitivity to diagnose Plasmodium infections compared with the study reported in China might be because the parasite load found there was greater than 100 parasite/μL.…”
Section: Discussioncontrasting
confidence: 41%
“…The high sensitivity achieved using this CareStart Test was quite comparable with previous CareStart Tests that were reported to have 99.4% in Wondogenet, 14 95% in Kola Diba, 15 94.91% in Karachi, 16 99.4% in Sierra Leone, 17 and 100% in Ghana 18 ; however, it was higher than the study reported (89.68%) in China-Myanmar. 19 The higher sensitivity to diagnose Plasmodium infections compared with the study reported in China might be because the parasite load found there was greater than 100 parasite/μL.…”
Section: Discussioncontrasting
confidence: 41%
“…The high specificity findings in the present study were comparable to specificity findings reported in endemic areas of Nigeria (97.6%) [23], 96.21% in Karachi [26], 96% in Sierra Leone [27] and 94.2% in north-west Ethiopia [28], but relatively higher than 72% reported in Uganda [29]. The likelihood ratio of a test kit combines both the sensitivity and specificity into a single figure and usually indicates how the test result can reduce the uncertainty of a given diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…Plasmodium falciparum and Plasmodium vivax are the dominant Plasmodium species with 60–70% and 30–40% reported cases, respectively [4]. Currently, the main strategy for malaria control is quick and accurate diagnosis followed by effective treatment [7, 8]. Among the diagnosis methods, microscopy is considered the “gold standard” because it has high sensitivity, inexpensive to perform, allows Plasmodium species identification and quantification of parasite density [9, 10].…”
Section: Introductionmentioning
confidence: 99%